State’s Responsibility over Forest and Land Fires Causing Transboundary Haze Pollution in the Frame of ASEAN Agreement - Fajar Khaify Rizky; Suhaidi Suhaidi; Alvi Syahrin; Jelly Leviza (Jambe Law Journal, 2020)
This article aims to analyze the state’s responsibility over forest and land fires causing transboundary haze pollution according to the Asean Agreement on Transboundary Haze Pollution. A normative legal method is applied to help answer the problems of transboundary pollution which has been an international concern. The impact of haze pollution resulted from forest and land fires has triggered protests against Indonesian government and urged the sate’s liability as long as the impact of the haze pollution is concerned. Forest and land fires which caused transboundary haze pollution has infilcted losses and damage not only in Indonesia but also in other neighbouring countries, such as Malaysia and Singapore. State responsibility is a fundamental principle in international law applied when a country has violated boundaries, either directly or indirectly, which is harmful to other countries. In international environmental law, tansboudary air pollution caused by forest and land fires is contrary to the principles of international environmental law resulting in a state responsibility responsibility or liability. While responsibility refers to a legally regulated responsibility and the concept of international law, the liability refers to the indemnification of the other party’s loss. As a result of forest and land fires causing transboundary haze pollution, ASEAN member countries have agreed to form an AATHP (ASEAN Agreement on Transboundary Haze Pollution) agreement aiming at preventing and mitigating transboundary haze pollution